Catholic Youth and Political Engagement: The Need for a Hybrid Model of Mobilization - Perbawaningsih, Yudi; Widodo, Yohanes; Lukisworo, Agustinus Aryo (Jurnal The Messenger, 2025)
Purpose: This study investigates the relationship between social media use, political information-seeking, political attentiveness, political awareness, and political participation among Catholic youth in the Archdiocese of Semarang. It asks whether digital engagement leads to active civic involvement or remains confined to passive consumption.   Methods: A quantitative survey was conducted among Catholic youth, chosen for their civic engagement and digital activity shaped by Church-based political education. Correlation tests examined the links between social media use, political awareness, and participation, focusing on attentiveness, information-seeking, and involvement in electoral and non-electoral activities.   Findings: Although Catholic youth are highly active on social media, political engagement is selective and often passive. Political awareness is relatively high but does not translate into broad participation beyond elections. Political attentiveness strongly correlates with information-seeking, while awareness shows only a weak connection to actual participation. Barriers such as selective exposure, algorithmic curation, polarization, and the absence of sustained mobilization limit meaningful engagement.   Originality: This study contributes theoretically by situating digital political engagement within a faith-based context, demonstrating how religious identity intersects with media effects and political behavior. It offers a novel conceptual integration of political attentiveness, information-seeking, and faith-based civic identity into digital participation models. Unlike prior research that generalizes youth behavior, this study provides a culturally grounded analysis of Catholic youth, emphasizing the Church’s dual role as both enabler and constraint of political agency. A hybrid mobilization model is proposed, bridging institutional support with community-driven digital activism to enrich theories of youth civic engagement.